The SMART way to migrate replicated stateful services - Lorch, Jacob R.; Adya, Atul; Bolosky, William J.; Chaiken, Ronnie; Douceur, John R.; Howell, Jon; Douceur, John (JD); Lorch, Jay; Bolosky, Bill (Proceedings of the 2006 EuroSys Conference, 2006)
Many stateful services use the replicated state machine approach for high availability. In this approach, a service runs on multiple machines to survive machine failures. This paper describes SMART, a new technique for changing the set of machines where such a service runs, i.e., migrating the service. SMART improves upon existing techniques in three important ways. First, SMART allows migrations that replace non-failed machines. Thus, SMART enables load balancing and lets an automated system replace failed machines. Such autonomic migration is an important step toward full autonomic operation, in which administrators play a minor role and need not be available twenty-four hours a day, seven days a week. Second, SMART can pipeline concurrent requests, a useful performance optimization. Third, prior published migration techniques are described in insufficient detail to admit implementation, whereas our description of SMART is complete. In addition to describing SMART, we also demonstrate its practicality by implementing it, evaluating our implementation’s performance, and using it to build a consistent, replicated, migratable file system. Our experiments demonstrate the performance advantage of pipelining concurrent requests, and show that migration has only a minor and temporary effect on performance.